Embedded processor security - d'Auriol, Brian J.; Pathan, Al-Sakib Khan (2007)
A preliminary model is introduced in this paper whereby data and its associated security properties are treated as a single atomic unit of information in a hardware-only context. Security-tagged data allows each datum to be properly manipulated with a predictable assurance. This paper addresses the data modeling, process modeling and network modeling of the associated security-tagged data. This work is a part of a larger issue that instruction set architectures (ISAs) do not consider the information assurance implications in its operational environment.